Usability evaluation algorithm of sea area landmark - TIAN Zhaoxu; CHENG Yongmei; ZHANG Xiaodong; YANG Su; YAO Shun (Xibei Gongye Daxue Xuebao, 2022)
The landmarks encountered by a flight vehicle in its scene matching navigation are insufficient and distributed unevenly, thus being unable to effectively assist in its inertial navigation system (INS). Therefore, this paper proposes a novel algorithm for sea area landmark usability evaluation based on the probability model. The algorithm defines three types of sea area landmarks and gives their matching method and strategy. The visible range of each sea area landmark is determined according to its relative relations between each position and all landmarks in flight area, flight altitude, flight speed, camera field of view angle and INS drift error. The matching probability of different types of landmarks at different flight altitudes is calculated. Then the observable probability of each landmark is reckoned to give the probability cloud of the sea area landmark usability. The simulation results verify the effectiveness of the algorithm. The sea area landmark usability evaluation results can provide bases for INS to effectively utilize landmarks to perform route planning and realize long-time flight and high-precision navigation.